"Better attendance~ brighter futures"- sustainable approaches to school attendance - Squelch, Joan (ANZELA, 2011)
In May 2010 the Department of Education of Western Australia launched its Better Attendance: Brighter Future strategy. The strategy was developed in response to recommendations made by the Auditor General in a report in 2009 on Managing Student Attendance in Western Australian Public Schools in which is was noted that ‘of the more than 177 000 students in Years 1 to 10 in WA’s public schools in 2008, almost 49 000 (28 per cent) are at educational risk because they are not attending school regularly’.2 The new school attendance strategy is based on ‘the mutual obligations of schools, parents and communities’. To this end, the Minister for Education Dr Constable notes in the strategy that ‘[s]chools, families and communities must work together to protect our children and young people from the tragic consequences of poor school attendance’. The role of parents is of fundamental importance in ensuring school attendance: ‘parents who make regular attendance a priority are also helping their children to value learning and to accept responsibility’. The new strategy is clearly focused on developing and implementing sustainable practices that will ensure the continued improvement of school attendance and enhanced student engagement and learning, from which the community ultimately benefits.Associated with this initiative, is the implementation of the Parental Support and Responsibility Act 2008 (WA) that has as one of its primary objects ‘to support and reinforce the role and responsibility of parents to exercise appropriate control over the behaviour of their children’. The Act recognises the crucial role parents play in promoting and protecting the well-being of their children, which includes supporting their education and ensuring attendance at school. Parents have the ultimately legal responsibility for ensuring children attend school. However, the Act is underpinned by the principle of shared responsibility that ‘parents, family and the community have for the wellbeing of the child’. A key part of the Act is the provision of responsible parenting agreements and orders that may be initiated and used to actively engage parents and ensure that they carry out their parenting responsibilities in relation to their children’s education and well-being.Against this background, the purpose of the paper is twofold. Part I of the paper will discuss some critical issues relating to school attendance and consider approaches to sustainable school attendance, including the Better Attendance ~Brighter Futures strategy as an example of good practice. Part II of the paper will consider the role and efficacy of responsible parenting agreements and orders, and some issues relating to the prosecution of parents, with specific reference to the WA Parental Support and Responsibility Act 2008. The paper will conclude with lessons from policy and practice regarding sustainable approaches to improving and maintaining school attendance.